Hubungan Postur Kerja Tidak Ergonomis Dan Karakteristik Responden Dengan Muscoloskeletal Disorders (MSDS) Pada Pekerja Furniture Di Cv Nova Furniture Boyolali - Putri, Vista Rizki Anita, Tarwaka, PGDip.Sc.,M.Erg (2017)
Musculoskeletal Disorders becomes one of the most occupational illness which occurs in furniture worker. On the process of making furniture, worker will sustain some postures such as bending, squatting, repetitive and others. This research aims to study the relationship between non ergonomical work posture with Musculoskeletal Disorders of furniture workers at CV Nova Furniture Boyolali. The type of this research is observational analytic with a cross sectional approach. The population used in this research is workers who do sanding, assembling, machining and spraying, where 44 people are chosen by a purposive sampling technique. The work process during sanding, assembling, machining and spraying give a risk of causing MSDs due to erratic worker's posture in order to adjust to the existing equipment and objects such as bending, bowing, crooked and so forth. Data analysis is done by using Pearson Product Moment Test. The results shows that there is a correlation between non ergonomical work posture (p=0,000) and smoking habit (p=0,046) with Musculoskeletal Disorders, but Musculoskeletal Disorders have no relation with age (p=0,178), work experience (p=0,360) and exercise habit (p=0,257). Based on the research, need to efforts by administrative control such as stretching in the working hours.